The multistress‐induced Translocator protein (TSPO) differentially modulates storage lipids metabolism in seeds and seedlings. (16th August 2018) - Jurkiewicz, Pawel; Melser, Su; Maucourt, Mickaël; Ayeb, Haitham; Veljanovski, Vasko; Maneta‐Peyret, Lilly; Hooks, Mark; Rolin, Dominique; Moreau, Patrick; Batoko, Henri
Summary: Translocator proteins (TSPO) are conserved membrane proteins extensively studied in mammals, but their function is still unclear. Angiosperm TSPO are transiently induced by abiotic stresses in vegetative tissues. We showed previously that constitutive expression of the Arabidopsis TSPO (AtTSPO) could be detrimental to the cell. Degradation of AtTSPO requires an active autophagy pathway. We show here that genetic modifications of TSPO expression in plant and yeast cells reduce the levels of cytoplasmic lipid droplets (LD). Transgenic Arabidopsis seedlings overexpressing AtTSPO contain less LD as compared with wild type (WT). LD levels were increased in Arabidopsis AtTSPO knockout (KO) seedlings. Deletion of the Schizosaccharomyces pombe TSPO resulted in an increase in LD level in the cell. As compared with the WT, the mutant strain was more sensitive to cerulenin, an inhibitor of fatty acids and sterol biosynthesis. We found that in contrast with seedlings, overexpression of AtTSPO (OE) resulted in an up to 50% increase in seeds fatty acids as compared with WT. A time course experiment revealed that after 4 days of seed imbibition, the levels of triacylglycerol (TAG) was still higher in the OE seeds as compared with WT or KO seeds. However, the de novo synthesis of phospholipids and TAG after 24 h of imbibition was substantially reduced in OE seeds as compared with WT or KO seeds. Our findings support a plant TSPO role in energy homeostasis in a tissue‐specific manner, enhancing fatty acids and LD accumulation in mature seeds and limiting LD levels in seedlings. Significance Statement: The Arabidopsis translocator protein (AtTSPO) is found in dry seeds but is only transiently induced by abiotic stresses. Constitutive expression of AtTSPO in vegetative tissues decreases the level of lipid droplets in the cell. In contrast, transgenic Arabidopsis seeds overexpressing AtTSPO contained up to 50% more triacylglycerol than wild‐type seeds, suggesting that this stress‐induced protein can differentially modulate triacylglycerol content in a cell‐type‐dependent manner in the plant.